THE URGENCY OF EDUCATION WITH CHARACTER IN TIME PANDEMIC COVID 19 - Bhatakavara Kumar; Mardhatillah Mardhatillah (SENSEI RESEARCH CENTER, 2021)
The aim of research is to write articles to describe the urgency of character education during the Covid 19 pandemic. Exemplary is an important aspect in realizing character education during the Covid 19 period, considering that character education is a form of personality that must be carried out in real terms in everyday life. Not only talking but must be proven in the form of excellence that is carried out by all parties. All components in schools and the State and parents must continue to work together to create patterns of behavior that are in accordance with the personality of the Indonesian nation amid the ongoing Covid-19 pandemic.